Optimizing treatment goals for long-term health outcomes among patients with type 2 diabetes mellitus - Lizheng Shi; Yilu Lin; Qian Shi; Vivian A Fonseca (BMJ Open Diabetes Research & Care)
Introduction Considerable confusions on treatment target have resulted from recent changes in guidelines. Evidence in medical guidelines came from clinical trials with highly selected patients, whereas treatment goals may differ in some subgroups. This study aimed to assess optimal treatment goals (A1C, blood pressure, low-density lipoprotein cholesterol (LDL-C)) for patients with type 2 diabetes mellitus (T2DM), which lead to optimal health outcomes by different treatment strategies.Research design and methods A retrospective longitudinal study was conducted for veterans with T2DM by using US Veterans Affairs Administrative Database (2005−2015). Medical records were prepared for repeated evaluation performed at 6-month intervals and multivariate longitudinal regression was used to estimate the risk of microvascular and macrovascular complication events. Second-degree polynomial and splines were applied to identify the optimal goals in their associations with lowest risk of clinical outcomes, controlling for demographic characteristics, medical history, and medications.Results A total of 124 651 patients with T2DM were selected, with mean of 6.72 follow-up years. In the general population, to achieve the lowest risk of microvascular and macrovascular complication, the optimal goals were A1C=6.81%, LDL-C=109.10 mg/dL; and A1C=6.76%, LDL-C=111.65 mg/dL, systolic blood pressure (SBP)=130.60 mmHg, respectively. The optimal goals differed between age and racial subgroups. Lower SBP for younger patients and lower LDL-C for black patients were associated with better health outcomes.Conclusions Optimal treatment goals were identified and multi-faceted treatment strategies targeting hyperglycemia and hyperlipidemia and hypertension may improve health outcome in veterans with T2DM. In addition to guidelines’ recommended goals, health systems may examine their own large diverse patients with T2DM for better quality of care.